2016
DOI: 10.1002/pon.4215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring stigma as a barrier to cancer service engagement with breast cancer survivors in Kampala, Uganda

Abstract: Objective To understand the role of stigma in the delay of cancer service engagement by women with breast cancer in Kampala, Uganda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 12 publications
5
87
0
1
Order By: Relevance
“…VHTs and dispensary staff should be educated to recognize the signs and symptoms of breast cancer, to know the appropriate level of care for patient referral (currently level 5 or 6 until capacity is built at lower levels of the health system), and to deliver culturally appropriate health messages regarding breast cancer awareness to women 13‐16 . These efforts can be integrated into established systems; for example, prior research demonstrated the success of educational strategies in Uganda for improving outcomes for the management of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…VHTs and dispensary staff should be educated to recognize the signs and symptoms of breast cancer, to know the appropriate level of care for patient referral (currently level 5 or 6 until capacity is built at lower levels of the health system), and to deliver culturally appropriate health messages regarding breast cancer awareness to women 13‐16 . These efforts can be integrated into established systems; for example, prior research demonstrated the success of educational strategies in Uganda for improving outcomes for the management of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study conducted in Ghana identified low level of education and delayed care‐seeking behavior as risk factors for presenting with tumors larger than 5 cm . Similarly, other smaller studies have identified limited knowledge , stigma associated with a cancer diagnosis, lack of social and financial support, and seeking alternative treatment from traditional healers as risk factors for delayed presentation . Although the current literature identifies several factors associated with delayed breast cancer presentation and the need for breast education as a cornerstone for increasing awareness, more research is needed to understand the information gaps specific to the sociocultural setting.…”
Section: Introductionmentioning
confidence: 97%
“…Stigma not only increases the potential harm of the disease but also leads to unhealthy psychological and social statuses among patients. Because of stigma, some people avoid social interactions and even isolate themselves completely, thereby negatively affecting their clinical encounters, the effects of therapy, their marriages, and other aspects of their life . Stigmatized patients might blame and criticize themselves along with facing discriminated against by others; consequently, these patients may feel ashamed, and their mental states might worsen, thereby reinforcing a vicious cycle …”
Section: Introductionmentioning
confidence: 99%
“…Because of stigma, some people avoid social interactions and even isolate themselves completely, thereby negatively affecting their clinical encounters, the effects of therapy, their marriages, and other aspects of their life. 5,6 Stigmatized patients might blame and criticize themselves along with facing discriminated against by others; consequently, these patients may feel ashamed, and their mental states might worsen, thereby reinforcing a vicious cycle. 7,8 One type of subjective feeling, coping self-efficacy, evaluates the coping strategies and methods a person uses when they face challenges.…”
mentioning
confidence: 99%